The Costs of Networked Learning - An interactive workshop - Ash, Charlotte; Bacsich, Paul (Proceedings of the International Conference on Networked Learning, 2000)
This workshop will be based heavily on the ongoing Costs of Networked Learning work undertaken by Sheffield Hallam University. Phase one of the study, which ran from January to June 1999, proposed a planning document and financial schema that together would accurately record the costs of networked learning. During phase one a number of issues were raised both by the study team and by other stakeholders. These issues need to be resolved during phase two of the project, starting later this spring, so that the framework offers the most acceptable solution to its potential users.